2018
DOI: 10.1007/s00192-018-3689-0
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic organ prolapse surgery following hysterectomy with benign indication: a national cohort study in Taiwan

Abstract: Hysterectomy may increase the risk of subsequent POP surgery, and various hysterectomy techniques, particularly VH and LAVH, may increase the risk of subsequent POP surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 19 publications
1
12
1
Order By: Relevance
“…Vaginal hysterectomies with suspension for treating POP lead to substantially higher rates of POP surgery than does the uterus preserving Manchester operation 1,2 . Likewise, a higher risk of POP surgery is found for hysterectomized women compared to non-hysterectomized women in studies of parous women 3,4 . This raises the question of whether the uterus protects against POP.…”
Section: Introductionmentioning
confidence: 98%
“…Vaginal hysterectomies with suspension for treating POP lead to substantially higher rates of POP surgery than does the uterus preserving Manchester operation 1,2 . Likewise, a higher risk of POP surgery is found for hysterectomized women compared to non-hysterectomized women in studies of parous women 3,4 . This raises the question of whether the uterus protects against POP.…”
Section: Introductionmentioning
confidence: 98%
“…Urodynamic studies are also not sensitive to detect subtle differences in urinary function [27]. Furthermore the association between clinical symptoms and urodynamics are poor [28]. Therefore, one may question the relevance of urodynamic testing rather than relying on patient reported outcomes by way of validated questionnaires.…”
Section: Discussionmentioning
confidence: 99%
“…Huang and Ding found that the risk of prolapse was doubled following hysterectomy over 10-years [28]. Observational studies show that the risk of vault prolapse is higher with VH and LAVH which is probably due to the fact that these patients would have had some degree of pelvic floor weakness which would have contributed to the decision to undergo a vaginal procedure [29].…”
Section: Discussionmentioning
confidence: 99%
“…5 Vaginal hysterectomy has been linked to an increased risk for POP surgery later in life. 6,7 By definition, apical prolapse, which can be graded by the Pelvic Organ Prolapse Quantification system (POP-Q) classification, is described as a descent of the uterus, the vaginal vault or the cervix after a total/subtotal hysterectomy. 8 In surgical repair of POP, the recurrence rate is about 30% and the importance of apical support was recently highlighted.…”
Section: Introductionmentioning
confidence: 99%
“…Age, parity, obesity and chronic lung conditions are other risk factors in the development of pelvic organ prolapse (POP) 5 . Vaginal hysterectomy has been linked to an increased risk for POP surgery later in life 6,7 …”
Section: Introductionmentioning
confidence: 99%